2011
DOI: 10.1111/j.1744-9987.2010.00848.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Thrombophilia in Vascular Access Thrombosis Among Chronic Hemodialysis Patients in Tunisia

Abstract: Vascular access thrombosis represents a serious and common problem in hemodialysis patients. Therefore, identification of relevant thrombotic risk factors could lead to an improved antithrombotic therapy. This case control study was performed to evaluate the relationship between some thrombophilias and vascular access thrombosis in hemodialysis patients. Seventy-eight patients undergoing dialysis (between May 2007 and September 2009) were selected as subjects. This sample was divided into two groups; a case gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
1
6
0
1
Order By: Relevance
“…Some studies, in agreement with the present study, did not find a significant association between the presence of G20210A and vascular access thrombosis . Our previous study of 28 patients and 50 controls showed that carriers of the prothrombin G20210A mutation did not have a significantly higher risk of VAT . In contrast, other studies suggest that the G20210A mutation may in fact contribute to vascular access thrombosis .…”
Section: Discussionsupporting
confidence: 90%
“…Some studies, in agreement with the present study, did not find a significant association between the presence of G20210A and vascular access thrombosis . Our previous study of 28 patients and 50 controls showed that carriers of the prothrombin G20210A mutation did not have a significantly higher risk of VAT . In contrast, other studies suggest that the G20210A mutation may in fact contribute to vascular access thrombosis .…”
Section: Discussionsupporting
confidence: 90%
“…30 Consistent with these findings, Födinger et al observed that heterozygous carrier status for factor V Leiden does not appear a risk factor for VAT in hemodialysis patients, suggesting that this is possibly due to the fact that the activated protein C (APC) activity is increased in hemodialysis patients, so that the APC resistance ratios are close to the normal range in hemodialysis patients who are heterozygous for factor V Leiden. 31 Finally, Fekih-Mrissa et al 32 excluded a significantly increased risk among patients affected by genetic mutations of both factor V Leiden and prothrombin G20210A.…”
Section: Inherited Thrombotic Risk Factorsmentioning
confidence: 99%
“…Further studies should focus on assessing the role of hemostatic alterations in the pathogenesis of ESRD. Thrombophilic risk factors were not only associated with vascular access thrombosis [30], but they may also contribute to significant morbidity after renal transplantation, thereby putting renal transplant recipients at a higher risk for early allograft loss.…”
Section: Discussionmentioning
confidence: 98%